The influence of brand ambassador and brand image on skincare products on purchase interest - Indra Kurniawan; Ledy Nimas Bidari (Enrichment : Journal of Management, 2023)
One way to increase consumer buying interest is to use brand ambassadors and increase product brand image. This study aims to determine the effect of brand ambassadors and brand image on the intention to buy Something products in Jombang Regency. Researchers used descriptive quantitative research methods involving respondents in filling out the questionnaire. The data collection technique uses a survey method with a questionnaire technique that is distributed directly to prospective consumers of Something's products. The sampling technique uses a non-probability sampling technique with a purposive sampling type with a total sample of 100 respondents. Data analysis technique using multiple linear regression analysis. The results of this study indicate that brand ambassadors have a positive and significant effect on consumer buying interest. That is, the higher the popularity of the brand ambassador used, the higher consumer buying interest tends to be. In addition, a significant influence was also found between brand image and consumer buying interest in Something products. A good brand image has the potential to influence consumers to make purchases. Thus, this study concludes that brand ambassadors and good image play an important role in increasing buying interest in Something products in Jombang Regency